SOCIAL ATTITUDES TO DRUGS ABUSE AMONG YOUTH AND DRUG ABUSE PREVENTION - Y. N. Nakhimova; G. F. Romashkina (Образование и наука)
Introduction. The formation of responsibility for one’s health in the youth environment is one of the tasks of the institution of education that determines the process of socialization. The future of sustainable development of country is determined, among other things, by the formation of negative social attitudes towards drug use.The aim of the publication is to study the specifics of the social orientation among young people on drug use and to justify the need for prevention in the educational environment.Methodology and research methods. Methodological basis of work involves classical theories of social installation; anomies; cultural conflict; subcultures; stigmatizations; social control; social space. The analysis and synthesis of scientific publications and data of the government statistics, including results of a number of social researches of 2010–2015 conducted in the Tyumen region are used. Sociological methods, including poll, questioning and the formalized interviews are applied at an experimental investigation phase. Data processing is carried out in technique of the factorial and classification analysis.Results and scientific novelty. Drug abuse among young people is a result of the contradiction between youth attitudes and social norms. It is shown that the prevention of drug abuse in Russia is institutionally ineffective. The social attitudes and motives connected with drug abuse among young people aged 18–30 years are revealed. It is established that acceptance of drug abuse experience is not defined by a gender, social and/or material status. The main types of the attitude to drug abuse experience are designated: 1) complete negation of a possibility of drug abuse; 2) refusal of drug abuse, but indifference or loyal attitude to drug abuse by others; 3) readiness for periodic drug usage; 4) steady stereotype of regular use of narcotic substances.The necessity of flexible forms of influence on youth for formation of sustainable social barriers is justified.The need of adequate public opinion formation which does not enable exclusion and criminalization among youth having some drug abuse experience is approved. Repressive practices of work with such young people only exacerbate the problem. The recommendations on organization regulation of a drug abuse situation in the country are formulated.Practical significance. The materials of the present article can be used for creation of effective system of drug abuse prevention in the educational environment taking into account age characteristics of pupils.